Design fires in road tunnels - Maevski, Igor Y. (Transportation Research Board, 2011)
"TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 415: Design Fires in Road Tunnels information on the state of the practice of design fires in road tunnels, focusing on tunnel fire dynamics and the means of fire management for design guidance"--Publisher's description
At head of title: National Cooperative Highway Research Program.
"A synthesis of highway practice."
Keywords: Tunnels -- Fires and fire prevention.; Tunnels -- Safety measures.; Roads -- Design and construction -- Safety measures.; Pavements -- Design and construction.; elektronické knihy; electronic books